2012
DOI: 10.1371/journal.pone.0031309
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Cardio-Metabolic Risk Factors in a Young Urban Sri-Lankan Population

Abstract: BackgroundSouth-Asian's are predisposed to early onset type 2 diabetes (T2DM). The prevalence of cardio-metabolic risk-factors in young Sri-Lankans is unknown.Methodology/Principal FindingsTo determine by questionnaire and anthropometry the prevalence of first degree family history (FH) of T2DM, physical inactivity, raised waist circumference (WC) and raised body mass index (BMI) in a representative healthy urban population selected by cluster sampling. Those with ≥2 risk-factors were evaluated for metabolic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
0
13
1
Order By: Relevance
“…35 Many reports have shown clustering of cardiometabolic risk factors in adolescence and HOMA-IR and waist circumference were important contributors to these cardiometabolic abnormalities within these clusters. 30,[36][37][38] Vikram et al 39 studied correlates of T2DM in the young in North India and concluded that early identification through simple anthropometric parameters such as waist circumference may be useful for planning primary prevention in this population.…”
Section: Discussionmentioning
confidence: 99%
“…35 Many reports have shown clustering of cardiometabolic risk factors in adolescence and HOMA-IR and waist circumference were important contributors to these cardiometabolic abnormalities within these clusters. 30,[36][37][38] Vikram et al 39 studied correlates of T2DM in the young in North India and concluded that early identification through simple anthropometric parameters such as waist circumference may be useful for planning primary prevention in this population.…”
Section: Discussionmentioning
confidence: 99%
“…National diabetes programmes have been initiated in Bangladesh [38], India [39], Pakistan (40) and Sri Lanka [41]. Nepal is developing strategies to implement similar national programmes [42].…”
Section: Successesmentioning
confidence: 99%
“…The National Diabetes Centre of Sri Lanka, with the collaboration of the scientists at King’s College, London, UK, has reported a high prevalence of risk factors for Type 2 diabetes in youth and adults aged 10–40 years [41]. The study is part of a research programme aimed at creation of awareness and developing methods to prevent diabetes in young Sri Lankans.…”
Section: Successesmentioning
confidence: 99%
“…Prevalence of metabolic syndrome has been reported to be between 12.8% to 41.1% in different parts of the world (10,11). Studies in Sri Lanka showed that the prevalence of metabolic syndrome was between 27.1% to 29.5% (12,13). Many factors including: female gender, increasing age, urban living, higher socio-economic status and physical inactivity were reported as important associated factors (12).…”
Section: Original Papermentioning
confidence: 99%